God : a story of Revelation - Chopra, Deepak (HarperOne, 2012)
In Deepak Chopra's new work, a unique blend of storytelling and teaching, the" New York Times" bestselling author explores the evolution of God. By capturing the lives of ten historical prophets, saints, mystics, and martyrs who are touched by a divine power, Chopra reveals a riveting portrait of a constantly changing God. Our belief--and therefore God itself--transforms with each passing century.